Temporary oral anticoagulation after MitraClip – a strategy to lower the incidence of post-procedural stroke?. Issue 1 (2nd January 2020) - Geis, Nicolas; Raake, Philip; Kiriakou, Christina; Mereles, Derliz; Frankenstein, Lutz; Abu-Sharar, Haitham; Chorianopoulos, Emmanuel; Katus, Hugo A.; Bekeredjian, Raffi; Pleger, Sven T.
Abstract: Background: Incidence of stroke within 30 days after percutaneous mitral valve repair using the MitraClip varies from 0.7% and 2.6% between registries. Standard medical treatment after the MitraClip procedure, in the absence of risk factors requiring antithrombotic therapy such as atrial fibrillation, is dual antiplatelet therapy using aspirin and clopidogrel. ESC/EACTS and ACC/AHA surgical guidelines show a Class IIa indication for temporary antithrombotic therapy after mitral valve repair/bioprosthetic valve replacement within the first three months even in patients with no additional risk factors. Methods : 470 patients were treated with the MitraClip receiving oral anticoagulation (Coumadin: INR 2.0–3.0) instead of dual antiplatelet therapy for at least 30 days after the procedure. The incidence of stroke, as well as major adverse events such as bleeding, were analysed in comparison to large registries and multi-centre studies. Results: Incidence of stroke within 30 days was significantly reduced as compared to comparative cohorts (0.2% vs. Median 1.3% [0.7–2.6%]; p < .05). Cardiovascular risk factors such as age, atrial fibrillation, hypertension, diabetes, STS score and prior stroke did not differ significantly between cohorts (ns). Bleeding complications were not increased due to 30 days oral anticoagulation treatment (4.6% vs. Median 7.4% [3.4–13.6%]; ns). Conclusions: Temporary oral anticoagulation might be a strategy to reduce the incidence of stroke within the first 30 days after the MitraClip procedure. Bleeding events were not significantly altered due to temporary oral anticoagulation.